Two new species of the genus Platambus Thomson, 1859 from China (Coleoptera: Dytiscidae, Agabinae) - Hendrich, Lars; Przewoźny, Marek (Zootaxa, 2015)
One new species of the genus Platambus Thomson, 1859 from Ganzi Tibetan Autonomous Prefecture, Sichuan Province (P. brancuccii sp. n.) and one from Chengdu, Sichuan Province (P. korgei sp. n.) are described. They belong to the Platambus semenowi-group sensu Nilsson (2000). Important species characters (median lobes and colour patterns) of the two new species are figured, and notes on their distribution are given. Altogether seven species of the semenowi-group are now known from higher mountain regions in Central Asia, northern India, Nepal, Bhutan, Pakistan and China. Six of them are illustrated with habitus photos and a modified key to all species of the semenowi-group is presented.